Exploring the Territorial Jurisdiction of Cybercrime in the ICC: An Application of the Doctrine of “Effects” - Huang, Zilan (Transactions on Social Science, Education and Humanities Research, 2024)
The doctrine of “effects”, as an objective application of territorial jurisdiction, has been controversial since its establishment. The dispute becomes more intense when it comes to cybercrime. In the area of International Criminal Law, while some practices in the international criminal court and tribunals indicate a trend towards expanding territorial jurisdiction, which implies the application of the “effects” doctrine, whether the Court can adopt the doctrine or not remains uncertain. In the background that the integration of cybercrime and crimes stipulated by the Court is becoming a trend, considering the necessity and feasibility of applying the “effects” doctrine to the International Criminal Court, it is argued that the doctrine should be applied to the Court’s territorial jurisdiction. However, some potential risks raised by the application require a more balanced solution for the problem, which means the “effects” doctrine can only be applied by the Court when there exists a substantial and reasonably foreseeable effect on the territory.